Inventarisasi Dan Analisis Jenis Tumbuhan Famili Euphorbiaceae Dan Sebarannya Di Desa Cipeundeuy, Kecamatan Bantarujeg, Kabupaten Majalengka - Fikri Iqlilah Gunawan; Fani Wilma Mulyana; Ateng Supriyatna (Pusat riset dan Inovasi Nasional, 2023)
Plant classification exists to simplify and clarify the level of kinship and the type of treatment in plant distribution, at the taxonomic level there are family categories, this family in plant taxonomy is a classification system that groups plants based on similarities between their morphology, characteristics, morphology. Euphorbiaceae is a family with flower characteristics hidden in cyathia structures (inflorencia), sap and various sizes. This research is located in Cipeundeuy Village, Bantarujeg District, Majalengka Regency with quantitative analysis using the exploration method in the residents' yards in Cipeundeuy Village. The results of the study found 1 individual of Ephorbia milli, 1 individual of Euphorbia hirta, 1 individual of Pedilanthus tithymaloides, 4 individuals of Acalypha siamensis and 8 individuals of Manihot esculenta from the Euphorbiacea family. This plant is used as an ornamental plant and can be used as herbal medicine because it has chemical compounds that are antiseptic, anti-inflammatory and antibacterial because it contains tannins, flavonoids and saponins which are effective for healing wounds and several other diseases. The purpose of this research is to inventory and identify plants in Cipeundeuy Village so that the systematics of plants in this area can be known.